In Vitro and In Vivo Evaluation of Niosomal Formulation for Controlled Delivery of Clarithromycin - Shilakari Asthana, Gyati (Scientifica (Cairo), 2016)
The present study was focused on formulating and evaluating clarithromycin (CLR) containing niosomal formulation for in vitro and in vivo pharmacokinetic behavior. Niosomal formulations (empty and drug loaded) were prepared by using different ratio of surfactant (various Span grades 20, 40, 60, and 80) and cholesterol by thin film hydration method and were evaluated for in vitro characteristics, stability studies, and in vivo study. Dicetyl phosphate (DCP) was added to the niosomal formulation. Various pharmacokinetic parameters were determined from plasma of male SD rats. Span 60 containing niosomal formulation NC(2) (cholesterol to surfactant ratio 1 : 1) displayed highest entrapment efficiency with desired particle size of 4.67 μm. TEM analyses showed that niosomal formulation was spherical in shape. Niosomes containing Span 60 displayed higher percentage of drug release after 24 h as compared to other formulations. NC(2) formulation was found to be stable at the end of the study on storage condition. Various pharmacokinetic parameters, namely, AUC, AUMC, and MRT of niosomal formulation, were found to be 1.5-fold, 4-fold, and 3-fold plain drug, respectively. The present study suggested that niosomal formulations provide sustained and prolonged delivery of drug with enhance bioavailability.